PENGARUH INVESTASI, PAD DAN DAU TERHADAP PERTUMBUHAN EKONOMI DI KABUPATEN/KOTA PROVINSI BALI - Putra, I Putu Herry Mahendra; Sutrisna, I Ketut (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 11 No 4 (2022): Vol. 11 No. 4, April 2022 [1215-1619]DO - 10.24843/EEP.2022.v11.i04.p01, 2022)
The occurrence of disparities in economic growth in the districts/cities of Bali Province. This study aims to analyze and determine the effect of investment, local revenue (PAD), and general allocation funds (DAU) on economic growth in the districts/cities of Bali Province and to determine the dominant variables affecting economic growth. The data source is secondary data using panel data consisting of time series data for five years and cross section data of nine districts/cities that produce 45 observations. The analytical technique used in this research is the multiple linear regression analysis model. The results of this study indicate that simultaneously investment, local revenue (PAD), and general allocation funds (DAU) have a significant effect on economic growth in the districts/cities of Bali Province. Local revenue (PAD) is the dominant variable that influences economic growth in Bali Province. Keywords: economic growth, investment, PAD, DAU